Taxonomic Note and Neotypification of Euonymus acutangulus Wight. (Celastraceae: Celastroideae) - Mondal, Ajay; Murugan, C. (Phytotaxa, 2024)
The correct name for the Indian endemic species currently referred to Euonymus angulatus Wight is demonstrated to be E. acutangulus Wight. A Neotype is designated for the name E. acutangulus, while E. angulatus and E. pterocladus are lectotypified in accordance with the Shenzhen Code.